Survival of egg, neonate and wandering-phase larvae of the Indianmeal moth (Plodia interpunctella (Hubner)) exposed to surface and aerosol applications of methoprene - Jenson, Emily A. (Kansas State University, 2008)
The Indianmeal moth, Plodia interpunctella Hubner, is capable of infesting a number of different commodities including a wide variety of grains, nuts and finished stored products. Therefore, control of the Indianmeal moth is especially needed in areas where food is being stored for human consumption. Increased concerns of consumers and producers regarding the impact of conventional insecticides on the environment and on human health has prompted scientists and the agricultural chemical industry to search for insecticides that do not affect mammalian nervous systems and have limited effects on non-target organisms. One group of insecticides with reduced risks is insect growth regulators (IGRs), which are substances that mimic insect hormones essential to normal development and reproduction. Currently methoprene, a juvenile hormone analog, is labeled for direct application to stored grains, as well as a contact insecticide and as an aerosol application inside mills, warehouses, and indoor food storage facilities. Surface treatments and aerosol space applications can be effective ways to treat the interior surfaces and storage areas of warehouses and food processing facilities. There is little recent research with large-scale aerosol applications in storage sites; furthermore, there are no published references in the scientific literature regarding efficacy of using methoprene alone in aerosol form. Therefore, the purpose of this research was to evaluate the use of surface and aerosol applications of methoprene on finished stored-product packaging materials and facilities for the control of P. interpunctella. Results of this research showed that while methoprene has good residual activity, and efficacy is unaffected by temperature, surface applications of methoprene on packaging materials is not as effective for control of P. interpunctella as aerosol applications of methoprene. Aerosol methoprene is highly effective alone and in combination with conventional chemicals for control of eggs and wandering-phase larvae. Simulations with a population growth model make it possible to estimate impact of insecticide treatments at different temperatures and application times on populations of P. interpunctella. Aerosol treatments are also economically viable as part of an overall integrated pest management program.
Keywords: Indianmeal moth; methoprene; integrated pest management; Biology, Entomology (0353)